Fourth-order conservative algorithm for nonlinear wave propagation: The rosenau-KdV equation - Rakbhoom Chousurin (2020)
© 2019 by the Mathematical Association of Thailand. All rights reserved. In this paper, we introduce a conservative difference method for solving the Rosenau-KdV equation. The existence of the approximate solution from the difference scheme is shown. We also prove the stability and convergence of this scheme. The presented method gives second-and fourth-order accurate in time and space, respectively. Numerical examples demonstrate the theoretical results.